Multi-feed spatial power combining reflectarrays - Arpin, Frederic N (University of Ottawa (Canada), 2004)
In order to have increased bandwidth, future wireless communications systems will use millimeter-wave frequencies. Such systems will require antennas with relatively high gain and sources with sufficient power. Spatial power combining provides an attractive alternative to these issues. This thesis develops a means of combining the antenna and spatial power-combining functions in a single device. We formulate a design procedure that allows multiple feeds to illuminate a reflectarray that will give a single-beam. The reflectarray acts both as a spatial-power combiner and as the antenna. Unlike previous work that has been done on spatial power-combining reflectarrays, the proposed design does not involve the integration of any active devices. The new design procedure for a multi-feed spatial power-combining reflectarray was first applied to a two-feed reflectarray which was fabricated and tested as a proof of concept. (Abstract shortened by UMI.)
Keywords: Engineering, Electronics and Electrical.